An Empirical Study on the Importance of electronic Word of Mouth in the Luxury Concierge Industry: the Case of Cyprus - Makrides, Anna; Vrontis, Demetris; Christofi, Michael (My University, 2020)
The widespread access of electronic word of mouth (e-WOM) enables contemporary consumers to assess the opinions of others, irrespective of geographical boundaries, about products and services. This research examines the impact of e-WOM on building international brand awareness when the former is used as a core part of a company's overall digital marketing strategy. By applying the survey methodology, the findings provide support for this positive effect; namely, the integration of e-WOM in the overall digital marketing strategy and activities applied by an organization can enhance brand awareness beyond country borders and contribute towards the overall organizational effectiveness and success. Taken together, the study provides further insight into eWOM and cross-border brand awareness relationship and outlines several questions that deserve further study.
Keywords: Electronic word of mouth; International brand awareness